PELAKSANAAN MAGANG BAGI CALON NOTARIS PADA KANTOR NOTARIS DIKAITKAN DENGAN KETENTUAN PASAL 16A UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS DI KABUPATEN DELI SERDANG - IRE TANARI PERANGIN ANGIN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. Jelly Leviza, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHum According to the Law on Notary Position No. 2/2014 on the Amendment to the Law No. 30/2004 on Notary Position, there is extra time for internship period from earlier 12 months to 24 months, in addition, article 16 A regulates the obligations of a notary candidate without any explanation about their authorities. This is an empirical juridical research with descriptive analysis. It is supported with interview results with 5 notaries as informants and 2 notary candidates in their internship term as respondents. The theory employed is this research is the theory of legal effectiveness and theory of rights and obligations. The results of the research demonstrate that the extra time for internship term from earlier 12 months to 24 months is not effective for the notary candidates. It is proven in the extra collective internship which is made compulsory by the Notary Association of Indonesia whish is done simultaneously with their internship in notary office. The internship itself has some obstacles.Keywords: Implementation, Internship, Notary Candidate, Notary